2013
DOI: 10.7863/ultra.32.6.915
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low‐Intensity Pulsed Ultrasound on Bone Morphogenetic Protein 7–Induced Osteogenic Differentiation of Human Nonunion Tissue‐Derived Cells In Vitro

Abstract: These findings show a significant effect of low-intensity pulsed US on the osteogenic differentiation of nonunion tissue-derived cells induced by BMP-7. This study may provide substantial evidence for the clinical combined application of BMP-7 and low-intensity pulsed US for nonunion treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The electronic search of the literature retrieved 1532 citations, but only 21 of them met the selection criteria 14 , 18 , 19 , 22 , 30 , 35 , 37 – 51 . Another three eligible papers 32 , 52 , 53 were obtained from the hand search of the references of the eligible studies and relevant review articles, yielding 24 eligible studies for the final analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The electronic search of the literature retrieved 1532 citations, but only 21 of them met the selection criteria 14 , 18 , 19 , 22 , 30 , 35 , 37 – 51 . Another three eligible papers 32 , 52 , 53 were obtained from the hand search of the references of the eligible studies and relevant review articles, yielding 24 eligible studies for the final analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another three eligible papers 32 , 52 , 53 were obtained from the hand search of the references of the eligible studies and relevant review articles, yielding 24 eligible studies for the final analysis (Fig. 1 ) 14 , 18 , 19 , 22 , 30 , 32 , 35 , 37 – 53 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have revealed that fracture healing is a complicated and consecutive process (7,8). At bone nonunion, hematoma and tissues between the fracture ends gradually develop into tissues between the fracture ends of bone nonunion (9). Tissues and hematoma join the fracture ends and in vitro its reaction is similar to that of bone mesenchymal stem cells.…”
Section: Introductionmentioning
confidence: 99%